2016
DOI: 10.2134/jeq2015.09.0482
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Phosphorus Runoff and Leaching from Poultry Litter with Alum: Twenty‐Year Small Plot and Paired‐Watershed Studies

Abstract: Treating poultry litter with alum has been shown to lower ammonia (NH) emissions and phosphorus (P) runoff losses. Two long-term studies were conducted to assess the effects of alum-treated poultry litter on P availability, leaching, and runoff under pasture conditions. From 1995 to 2015, litter was applied annually in a paired watershed study comparing alum-treated and untreated litter and in a small plot study comparing 13 treatments (an unfertilized control, four rates of alum-treated litter, four rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 43 publications
(62 reference statements)
6
50
0
2
Order By: Relevance
“…In China, overapplication of manure has produced undesirable impacts on water quality (Wu and Chen 2013; Chadwick et al, 2015). Alum has been proven to be highly effective for immobilizing P in chicken manure or litter (Moore et al, 2000; Huang et al, 2016). This was confirmed in the current study, particularly for WSRP (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In China, overapplication of manure has produced undesirable impacts on water quality (Wu and Chen 2013; Chadwick et al, 2015). Alum has been proven to be highly effective for immobilizing P in chicken manure or litter (Moore et al, 2000; Huang et al, 2016). This was confirmed in the current study, particularly for WSRP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is now well understood that long‐term application of animal manure will increase both the reactive (RP) and nonreactive P (NRP) pools in soils receiving the manure (Pagliari and Laboski 2013, 2014; Waldrip et al, 2015). For example, Eghball et al (1996) found that available P increased to a soil depth of 1.8 m after 40 yr of manure application, whereas Huang et al (2016) observed a significant increase in Mehlich‐3 P in the soil profile after 20 yr of poultry litter application. Phosphorus accumulation in soils increases the potential risk for P loss, which has been defined as a major environmental threat to receiving aquatic ecosystems (Schroeder et al, 2004; Wu and Chen, 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Low dissolved concentrations of Al and Fe in the study ponds were consistent with levels found in regional ponds (Table 1; Mattson et al, 1992), likely increasing P removal efficiency of Al and Fe based treatments (Leytem and Bjorneberg, 2005). Given the relatively low Ca and P concentrations, as well as the slightly acidic pond water pH (Table 1), precipitation of Ca‐P could be suppressed in pond water used for cranberry production (Jenkins et al, 1971; Diaz et al, 1994; Song et al, 2002). …”
Section: Resultsmentioning
confidence: 99%